IL-21 and anti-CD40 restore Bcl-2 family protein imbalance in vitro in low-survival CD27+ B cells from CVID patients. Issue 12 (December 2018) - López-Gómez, Antonio; Clemente, Antonio; Cunill, Vanesa; Pons, Jaime; Ferrer, Joana
Abstract Common variable immunodeficiency (CVID) is characterized by an abnormal B cell differentiation to memory and antibody-secreting B cells. The defective functionality of CVID patients' B cells could be the consequence of alterations in apoptosis regulation. We studied the balance of Bcl-2 family anti-/pro-apoptotic proteins to identify molecular mechanisms that could underlie B cell survival defects in CVID. We used flow cytometry to investigate Bcl-2, Bcl-XL, Bax, and Bim expression in B cells ex vivo and after anti-CD40 or anti-BCR activation with or without IL-21, besides to spontaneous and stimulation-induced Caspase-3 activation and viable/apoptotic B cell subpopulations. We found increased basal levels of Bax and Bim in CVID B cells that correlated with low viability and high Caspase-3 activation only in CD27+ B cells, particularly in a subgroup of apoptosis-prone CVID (AP-CVID) patients with low peripheral B cell counts and high autoimmunity prevalence (mostly cytopenias). We detected a broad B cell defect in CVID regarding Bcl-2 and Bcl-XL induction, irrespective of the stimulus used. Therefore, peripheral CVID memory B cells are prompted to die from apoptosis due to a constitutive Bcl-2 family protein imbalance and defective protection from activation-induced apoptosis. Interestingly, anti-CD40 and IL-21 induced normal and even higher levels of Bcl-XL, respectively, in CD27+ B cells from AP-CVID, which was accompanied by cell viability increase. Thus low-survival memory B cells from AP-CVID can overcome their cell death regulation defects through pro-survival signals provided by T cells. In conclusion, we identify apoptosis regulation defects as disease-contributing factors in CVID. B cell counts and case history of cytopenias might be useful to predict positive responses to therapeutic approaches targeting T-dependent signaling pathways.